2023
DOI: 10.1038/s41598-023-42226-7
|View full text |Cite
|
Sign up to set email alerts
|

Woody plant encroachment modifies carbonate bedrock: field evidence for enhanced weathering and permeability

Pedro A. M. Leite,
Logan M. Schmidt,
Daniella M. Rempe
et al.

Abstract: Little is known about the effects of woody plant encroachment—a recent but pervasive phenomenon—on the hydraulic properties of bedrock substrates. Recent work using stream solute concentrations paired with weathering models suggests that woody plant encroachment accelerates limestone weathering. In this field study, we evaluate this hypothesis by examining bedrock in the Edwards Plateau, an extensive karst landscape in Central Texas. We compared a site that has been heavily encroached by woody plants (mainly Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Dodds et al, (2023), did not observe a change in stream flow and attributed this to woody encroachments' ability to permanently change soil structure and preferential flow paths. Consistent with observations made in Edwards Plateau, that as woody plants die the leave behind decaying roots that increase preferential flow (Leite et al 2023).…”
Section: Comparison To Other Systemssupporting
confidence: 89%
See 2 more Smart Citations
“…Dodds et al, (2023), did not observe a change in stream flow and attributed this to woody encroachments' ability to permanently change soil structure and preferential flow paths. Consistent with observations made in Edwards Plateau, that as woody plants die the leave behind decaying roots that increase preferential flow (Leite et al 2023).…”
Section: Comparison To Other Systemssupporting
confidence: 89%
“…Studies in Edwards Plateau include effects by woody encroachment on subsurface porosity, groundwater recharge and changes to stream flow. One of these studies concluded that in Edwards Plateau bedrock below woody plants has much higher permeability and can increase over time (Leite et al 2023).…”
Section: Comparison To Other Systemsmentioning
confidence: 99%
See 1 more Smart Citation